(untitled) - Schaperclaus, Wilhelm (Rotterdam, 1992)
This work first presents a general account of the various causes of fish diseases. The pathological phenomena and processes are considered in detail. Fish diseases are then arranged according to their pathogens.
Keywords: Fishes; Diseases